Recently published papers: The message is clear – start early? - Spivey, Mike (BioMed Central, 2004)
Recent papers discussed include a positive trial of early tracheostomy, two negative studies of targeted noninvasive ventilation, the long awaited results of the high versus low positive end-expiratory pressure Acute Respiratory Distress Syndrome Clinical Trial Network trial and a simple but illuminating study into prognostic markers and end-points of resucitation.